Food preferences in a generalist pollen feeder: A nutritional strategy mainly driven by plant carbohydrates - Bellec, Laura; Cortesero, Anne-Marie; Giguère, Thomas; Faure, Sébastien; Hervé, Maxime R. (Frontiers in Ecology and Evolution, 2022)
Animal nutritional strategies have been extensively studied in vertebrates, where generalism at the individual scale is the rule. In insect herbivores, the determinants of the nutritional strategy of individual-scale generalists remain poorly studied, and the focus has been placed mainly on the influence of plant defense. Moreover, the integration of a physiological dimension in such studies remains rare. Here, we investigated the determinants of the nutritional strategy of pre-diapausing pollen beetles, Brassicogethes aeneus, with a focus on the influence of macronutrients. Before their diapause, pollen beetles are known to feed from plants belonging to many different families. This raises three questions: (i) Is the generalism of pollen beetles a populational consequence of individuals specialized on different plant families? (ii) Do individuals feed at random on flowers available or do they have a particular nutritional strategy? (iii) In case of non-random feeding choices, do pollen macronutrients explain this nutritional strategy? To answer these questions, we used a series of laboratory experiments including feeding choice tests on flowers and artificial substrates, quantification of pollen nutrient content, quantification of the insect energetic budget and performance experiments. We show that pollen beetles are generalist at the individual scale, and that clear and stable food preferences are established over a few hours in a multi-choice context. Pollen beetles prefer to feed on flowers with a carbohydrate-rich pollen, and this preference is adaptive since performance correlates positively with the plant carbohydrate content. This better performance may be explained by the fact that individuals feeding on carbohydrate-rich resources accumulate more glycogen and total energetic reserves. This study represents one of the few evidences of generalism at the individual scale in an herbivorous insect. It provides a better understanding of the nutritional strategy of a non-bee pollen feeder and shows the importance of carbohydrates in this strategy. It highlights the need to combine assessments of the plant macronutrient content and insect energetic budget in an adaptive framework to better understand the nutritional strategies of herbivores.